DESAIN ALAT PEMASANGAN DAN PENCOPOT VALVE SPRING SEDERHANA DENGAN MENGGUNAKAN TEKANAN DARI IMPACT DRIVER (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2022)
The purpose of designing this tool is to create an alternative tool to install and remove the Valve Spring that is simpler and easier to use and more efficient, create a tool concept to install and remove the Valve Spring that is simpler and more effective which can then be used by the engineering tool manufacturing industry to create new tools, as well as to be able to help technicians as tool users by simplifying work and saving work time.